Pemanfaatan Media Digital dalam Meningkatkan Brand Awareness SociaBuzz - Thalia Tamara Desca; Satya Candrasari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Nowadays many well-known companies and offices have begun to analyze how to attract consumers or distributors to cooperate with them and how to also create an attractive promotion which can be said as a way to attract or attract consumers or distributors to their company. The purpose of this study was to determine SociaBuzz's marketing communication strategy in enhancing Brand Awarness. This study uses qualitative methods with data collection techniques through observation, interviews, telephone, voice note. The results of this study indicate that the marketing communication strategy undertaken by SociaBuzz by using several advertising channels, car adversiting also SociaBuzz uses SEO on page and of page. Researchers suggest that SociaBuzz broadens the reach of their marketing targets and develops better marketing strategies..